Lebanon-Determinants of Commercial Bank Deposits in a Regional Financial Center - Finger, Harald (IMF Working Papers; Working Paper, 2009)
This paper empirically examines the demand for commercial bank deposits in Lebanon, a regional financial center. With Lebanon's high fiscal deficits financed largely by domestic commercial banks that rely on deposit funding, deposit growth is a key variable to assess government financing conditions. At the macro level, we find that domestic factors such as economic activity, prices, and the interest differential between the Lebanese pound and the U.S. dollar are significant in explaining deposit demand, as are external factors such as advanced economy economic and financial conditions and variables proxying the availability of funds from the Gulf. Impulse response functions and variance decomposition analyses underscore the relative importance of the external variables. At the micro level, we find that in addition, bank-specific variables, such as the perceived riskiness of individual banks, their liquidity buffers, loan exposure, and interest margins, bear a significant influence on the demand for deposits.